Atezolizumab-Induced Sarcoidosis-Like Reaction in a Patient with Metastatic Breast Cancer. (27th January 2022) - Tsunoda, Akira; Mizuno, Toshiro; Iida, Shohei; Uchida, Katsunori; Yamashita, Masako; Sukeno, Koshi; Oka, Hiroki; Tono, Yasutaka; Ishihara, Mikiya; Saito, Kanako; Tamaru, Satoshi; Yamanaka, Keiichi; et al.
Abstract : Tumor-related sarcoidosis-like reactions (SLR) have been reported with the use of immune checkpoint inhibitors (ICIs). We report a case of 50-year-old woman who observed an enlarged lymph node in the right hilar region and the appearance of a subcutaneous mass in the extremities during chemotherapy with atezolizumab plus nab-paclitaxel for metastatic triple-negative breast cancer (TNBC). Skin biopsy revealed the formation of epithelioid granulation species with the Langhans giant cell. After discontinuing atezolizumab in the treatment procedure, the hilar lymph nodes and the subcutaneous mass were reduced. A pathological examination was effective in differentiating tumor exacerbation from SLR. Owing to limited information on ICI-related SLR in breast cancer, future studies are recommended to properly manage immune-related adverse effects during cancer treatment.